Urban Environmental Applications of GIScience: Challenges and New Trends - Ozbakir, Buket Aysegul (IGI GLOBAL, 2012)
Geographic Information Systems (GIS) are computer-based systems used to store and manipulate geographical data, and perform spatial analysis. These systems serve to reveal the patterns, relationships, and anomalies, or sometimes invisible characteristics of the geographical data in various applications. While the term GIS indicates an object or tool, GIScience, the acronym for Geographic Information Science, covers a broader context of methodologies behind spatial data analysis. Among different application areas of GIS, environmental monitoring and modeling plays a significant role in the development of the very first GIS in the world-The Canada Geographic Information Systems (CGIS) in the mid-1960s. After almost 40 years of history, significant changes and challenges took place in the geographic information research agenda. This chapter will point out some of the vital tools and methods used in GIScience (including GIS, remote sensing and 3D modeling) to grasp issues of our urban environments. With recent technological advances that facilitate our understanding of the environment; it is more evident that the vision of more livable cities is not too far but not easy as well.
Keywords: INFORMATION; QUALITY; LANDSAT; Science & Technology - Other Topics; Urban Studies